Understanding the youth tourists' motivation to attend rural gastronomic festivals in the Republic of Serbia - Seočanac Marijana (Ekonomika Poljoprivrede (1979), 2022)
This study aims to examine the motivation of young tourists to attend gastronomic festivals in rural areas in the Republic of Serbia. In addition, it seeks to find out whether their motivation differs depending on their knowledge of and interest in gastronomy. The research was conducted on a sample of 125 respondents. The collected data was analyzed through the Statistical Package for Social Sciences (SPSS 20), using descriptive statistics, the K-means clustering multivariate grouping technique, and nonparametric statistical procedures (Kruskal-Wallis H test and Mann-Whitney U test). The results have shown that the opportunity to try new and varied foods, as well as enjoying the atmosphere at the festival, are the main motives for young tourists to attend gastronomic festivals in rural areas in the Republic of Serbia. Additionally, it was discovered that the gastronomic motifs of young tourists are different and conditioned by their knowledge of and interest in gastronomy.